1994
DOI: 10.1038/370223a0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear protein CBP is a coactivator for the transcription factor CREB

Abstract: The transcription factor CREB binds to a DNA element known as the cAMP-regulated enhancer (CRE). CREB is activated through phosphorylation by protein kinase A (PKA), but precisely how phosphorylation stimulates CREB function is unknown. One model is that phosphorylation may allow the recruitment of coactivators which then interact with basal transcription factors. We have previously identified a nuclear protein of M(r)265K, CBP, that binds specifically to the PKA-phosphorylated form of CREB. We have used fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
994
4
7

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,384 publications
(1,037 citation statements)
references
References 19 publications
32
994
4
7
Order By: Relevance
“…The bromodomain appears to be highly conserved through evolution and is associated with many transcription factors having a role in histone acetylation including yeast and human GCN5 Candau et al, 1996;Georgakopoulos and Thireos, 1992;Wang et al, 1997), p300/CBP (Arany et al, 1994;Arias et al, 1994;Bannister and Kouzarides, 1996;Chrivia et al, 1993;Kwok et al, 1994;, pCAF and hTAF II 250 (Mizzen et al, 1996). It has, however, been shown by several groups that the bromodomain is dispensable for HAT activity Mizzen, 1996 #77;Ogryzko, 1996 #76).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bromodomain appears to be highly conserved through evolution and is associated with many transcription factors having a role in histone acetylation including yeast and human GCN5 Candau et al, 1996;Georgakopoulos and Thireos, 1992;Wang et al, 1997), p300/CBP (Arany et al, 1994;Arias et al, 1994;Bannister and Kouzarides, 1996;Chrivia et al, 1993;Kwok et al, 1994;, pCAF and hTAF II 250 (Mizzen et al, 1996). It has, however, been shown by several groups that the bromodomain is dispensable for HAT activity Mizzen, 1996 #77;Ogryzko, 1996 #76).…”
Section: Discussionmentioning
confidence: 99%
“…CBP contains a bromodomain and has been implicated in the t(11;16) translocation with MLL and in the t(8;16) translocation with MOZ (Borrow et al, 1996). CBP has been shown to mediate the transcription of cyclic AMP response element (CRE) or mitogen responsive genes (Arias et al, 1994;Chrivia et al, 1993;Kwok et al, 1994) and interact with the basal transcription apparatus through TFIIB (Kwok et al, 1994). CBP or its close homologue, p300, can also interact with p300/CBP associated factor (P/CAF) which, as part of a protein complex is capable of histone acetylation .…”
Section: Discussionmentioning
confidence: 99%
“…CREB binding protein (CBP) and the closely related coactivator p300 (collectively referred to as CBP/p300) have been shown to cooperate with a variety of transcriptional activating proteins to regulate speci®c gene transcription (Kwok et al, 1994;Lundblad et al, 1995;Arany et al, 1994;Arias et al, 1994). In particular, Bannister and Kouzarides (1995) showed that CBP directly interacted with c-Fos in vitro and could stimulate GAL4-Fos transactivation in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…CBP was originally reported as a coactivator of CREB (Chrivia et al, 1993;Kwok et al, 1994), however it turned out to be a multifunctional co-activator of various transcription factors, including c-Myb and GATA-1 (Blobel et al, 1998;Dai et al, 1996;Mink et al, 1997;Oelgeschlager et al, 1996). In this study, we reveal the inhibitory interaction of cMyb and GATA-1, which is probably mediated by CBP.…”
Section: Introductionmentioning
confidence: 57%